Difusão de inovações : o papel dos valores humanos sobre a inovatividade - Ogiwara, Renan Sahity Araújo (2017)
The theory of basic human values has been demonstrating, through an extensive body of literature it’s universality across different cultures, as well as it’s influence in the most of the motivated human behaviour (ROKEACH, 1973; SCHWARTZ, 1992, 2006). Through replication and expansion of Mansori, Sambasivan e Md-Sidin (2015) modelo used in Malaysia. The present study analysis through structural equations modeling the current structuring and effects of individual values, religiosity and ethnicity on the innate innovativeness and the acceptance of new products and services by the consumer in Brazil. The results confirm most of the theoretically proposed relationships of conflict and cohesion between the individual basic values, innate innovativeness and acceptance of new product and services by the consumer. Just as they demonstrate the mediation of the basic individual values of openness to change and selfenhancement between respondents religiosity and ethnicity. However, the results suggest that in Brazil religiosity and ethnicity are in fact an “exceptionality” and do not present a negative relation with innate innovativeness and the acceptance of new products and services as traditionally observed. Finally, it is known that the nature os human values is attributed both to individual experiences, to the social context and its practices - e.g. religion and culture (SCHWARTZ; HUISMANS, 1995; STEENKAMP; HOFSTEDE; WEDEL, 1999; VAN HERK; POORTINGA, 2012; BOER; FISCHER, 2013; SORTHEIX; LÖNNQVIST, 2014; BARDI et al. 2014; BOER; FISCHER, 2016). In the present study, the distribution of the basic individual values across the national territory is in line with the socio-economic history of the regions and their current social context, demonstrating that human values are also an adaptive resource. The present study reinforces the evidence on the direct and indirect association between human values, religiosity, ethnicity and consumer innovativeness (DAGHFOUS; PONS, 1999; MANSORI; SAMBASIVAN; MD-SIDIN, 2015). Further discussions, limitations and suggestions are addressed at the end of this research.